Prevention of serious events in adults 65 years of age or older: A comparison between high-dose and standard-dose inactivated influenza vaccines - DiazGranados, Carlos A.; Robertson, Corwin A.; Talbot, H. Keipp; Landolfi, Victoria; Dunning, Andrew J.; Greenberg, David P. (Vaccine, 2015)
•Randomized trial of high-dose vs. standard-dose influenza vaccines in older adults.•High-dose vaccine decreased the risk of serious cardio-respiratory events.•The relative effectiveness against serious pneumonia was 39.8%. A recent study showed that a high-dose inactivated influenza vaccine (IIV-HD) was 24.2% more efficacious than a standard-dose inactivated influenza vaccine (IIV-SD) in preventing laboratory-confirmed symptomatic influenza in adults ≥65 years. Here we evaluate the effectiveness of IIV-HD compared to IIV-SD in preventing serious illnesses considered potential sequelae or complications of influenza infection. The original study was a double-blind, randomized, active-controlled, multicenter trial. Participants were adults ≥65 years randomized to receive IIV-HD or IIV-SD, and followed for 6–8 months post-vaccination for the occurrence of influenza and serious adverse events (SAEs). SAEs were events: leading to death or hospitalization (or its prolongation); considered life-threatening or medically important; or resulting in disability. For the present analysis, reported SAEs were classified as possibly related to influenza by three blinded physicians and rates per 1000 participant-seasons were calculated. Relative vaccine effectiveness (rVE) was estimated as (1−Rate Ratio)×100. 31,989 participants were enrolled, with 15,991 and 15,998 randomized to receive IIV-HD and IIV-SD, respectively. IIV-HD was significantly more effective than IIV-SD in preventing SAEs possibly related to influenza overall (rVE, 17.7%; 95% confidence interval [CI], 6.6–27.4%) and serious pneumonia (rVE, 39.8%; 95% CI, 19.3–55.1%). Borderline significance was observed for the efficacy of IIV-HD relative to IIV-SD for the prevention of all-cause hospitalizations (rVE, 6.9%; 95% CI, 0.5–12.8%). Compared to IIV-SD, IIV-HD reduced the risk of SAEs possibly related to influenza. The observed relative effectiveness against serious pneumonia is particularly noteworthy considering the burden of influenza and pneumonia in older adults.